Socio-economic determinants of maternal health care utilization in Kailahun District, Sierra Leone, 2020 - Desmond Maada Kangbai; Delia Akosua Bandoh; Alexander Manu; Joetrice Yewah Kangbai; Ernest Kenu; Adolphina Addo-Lartey (BMC, 2022)
Abstract Background Ascertaining the key determinants of maternal healthcare service utilization and their relative importance is critical to priority setting in policy development. Sierra Leone has one of the world's highest maternal death ratios in the context of a weak health system. The objectives of this study were to determine; the level of utilization of Antenatal Care (ANC), Skilled Delivery Attendants (SDA), Postnatal Care (PNC) services, and factors that influence the utilization of these services. Methods We conducted a community-based cross-sectional study involving 554 women of reproductive age (15-49 years) who had at least one delivery in the last 3 years and lived in the Kailahun District, Sierra Leone from November 2019 to October 2020. Data were analysed using analysed using bivariate, multivariate and multinomial logistic regression models. Results The median age of respondents was 25 years (Q1 = 17 years, Q3 = 30 years). Eighty-nine percent (89%) had 4 or more ANC visits. Only 35.9% of women were delivered by SDA. Women residing in urban areas had over six-fold increased odds of utilizing SDA as compared to women residing in rural areas (AOR = 6.20, 95% CI = 3.61-10.63). Women whose husbands had a primary level of education had 2.38 times increased odds of utilizing SDA than women whose husbands had no education (AOR = 2.38, 95% CI = 1.30-4.35). Women that walked longer distances (30-60 min) to seek healthcare had 2.98 times increased odds of utilizing SBA than those that walked shorter distances (< 30 min) (AOR = 2.98, 95% CI = 1.67-5.33). Women who had a secondary/vocational level of education had 2.35 times increased odds of utilizing the standard PNC category as compared to those with no education (OR = 2.35, 95% CI = 1.19-4.63). Conclusion The majority of women had 4 or more ANC visits yet the use of skilled birth attendants was low. Urban residence and education were significantly associated with the use of the standard PNC category. To improve the utilization of maternal health care services, national healthcare policies should target the advancement of education, train skilled Maternal Healthcare (MHC) attendants, rural infrastructure, and the empowerment of women.